Cooperation of the State Bureau of Investigations with International Organizations and Networks in the Sphere of Combating Crime - Lysakovskyi, Roman (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
Combating crime is one of the tasks of law enforcement agencies, which correlates with the role and importance of the functioning of these agencies for society. Each law enforcement agency has its own specifics of organization and activity, but the common thing is that in the process of implementing legally established functions, they cooperate with the relevant law enforcement agencies of other states, as well as international organizations and networks. This is due to the significant spread of cross-border crimes, as well as the complexity of their detection and investigation. The purpose of the article is to analyze the cooperation of the State Bureau of Investigation with international organizations and networks in the field of combating crime. The main strategic directions of cooperation of the State Bureau of Investigation are determined, i.e.: improvement of bilateral cooperation with the EU Representation in Ukraine, the EUAM on reforming the civil security sector of Ukraine, the Office of the Council of Europe in Ukraine, other international partners with the aim of building the institutional capacity of the SBI, implementing the best global standards of law enforcement activities in the work of the SBI; the development of the normative and legal framework, which regulates the international cooperation of the SBI with law enforcement agencies of other states and international organizations; effective cooperation with the Council of Europe and the Office of the Council of Europe in Ukraine, the UN Human Rights Monitoring Mission in Ukraine, the Coordinator of OSCE projects in Ukraine, other international organizations in the fight against torture and other types of ill-treatment; implementation of international technical assistance projects. The key principles of cooperation of the State Bureau of Investigation within Interpol and Europol are characterized. The contribution of the Council of Europe to cooperation with law enforcement agencies of its member states within the framework of international conventions are researched. Forms of cooperation of the State Bureau of Investigation with international organizations and networks in the field of combating crime are clarified.